PENDIDIKAN KARAKTER DISIPLIN DI SEKOLAH DASAR - Kristiyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background to this research is the low cognitive learning outcomes in class V Natural and Social Sciences at SDN 1 Kendengsidialit. As many as 37% of students have achieved the Minimum Completeness Criteria (KKM). This is due to the lack of variation in the use of learning models and media. The formulation of the problem in this research is "Application of the Project Based Learning Model Assisted by Audio Visual Media to Improve the Learning Outcomes of Class V Students at SDN 1 Kendengsidialit in Natural and Social Sciences Subjects." This research is a classroom action research with the research subjects being class V students at SDN 1 Kendengsidialit Welahan Jepara, totaling 27 people. The data collection technique for this research is a test technique. The research results show that the use of the Project Based Learning model assisted by Audio Visual media can improve student learning outcomes. This can be seen from the increase in the percentage of completeness of students' learning outcomes with the predetermined success indicators, namely a minimum of 75%. In Pre-cycle I, the percentage of students' completion was 37%. Cycle I experienced an increase of 70%, and cycle III of 93%. It was concluded that the Project Based Learning model assisted by audio visual media could improve student learning outcomes in Chapter 2 Harmony in Ecosystems for class V semester 1 of SDN 1 Kendengsidialit Welahan jepara.